Effects of Heavy Metal (Pb) on the Growth of Algae Microcystis sp. & Chroococcus sp. Roaa Jafar El-Khairalla - Roaa El-Khairalla (University of Thi-Qar Journal of Science, 2019)
The Study dealing with the influence of heavy metal(Pb) separately in the growth of the algae Microcystis & chroococcus (cyanophyta)under lab. Conditions,the parameters were total cell count by slid chamber.The resultsindicates that the toxic effect of studied heavy metals depend upon metal construction,lowest total cell count . leadions was added to the culture media as aconcetration (0.5, 1, 2,4)mg/l . the (4)mg/l concentration was more toxicityfor both algae , the minimum chroococcus colonies count was (62) colony and (66) colony in microcystis at (4) mg/lconcentration. By measuring inhibit rate for both algae,found , Microcystis was more resistant lead than otheralgae.Obsorved increase toxisity increased period was concentration of 4% toxcisity for both algae.